Mystery Science Theater 3000 presents. The leech woman [videorecording (DVD)] - Murphy, Kevin, 1956-; Nelson, Michael J.; Beaulieu, Trace, 1958-; Mallon, Jim director ([publisher not identified], 2013)
In celebration of the 25th anniversary of the series, see four never-before-released episodes and two long-out-of-print episodes that marked the seismic transition that occurred when Joel passed the torch on to Mike.